Insect development under predation risk, variable temperature, and variable food quality - J. David Logan; William Wolesensky; Anthony Joern (Mathematical Biosciences and Engineering)
We model the development of an individual insect, a grasshopper, through its nymphal period as a function of a trade-off between prey vigilance and nutrient intake in a changing environment. Both temperature and food quality may be variable. We scale up to the population level using natural mortality and a predation risk that is mass, vigilance, and temperature dependent. Simulations reveal the sensitivity of both survivorship and development time to risk and nutrient intake, including food quality and temperature variations. The model quantifies the crucial role of temperature in trophic interactions and development, which is an important issue in assessing the effects of global climate change on complex environmental interactions.